Implementasi Maqāṣid Al-Sharīah dalam Tradisi Topeng Konah di Bondowoso - Arifin, Mohammad Samsul; Munir, Muhammad Sirajul; Habibi, Erfan; Juhariyanto, Muhammad (Proceedings of Annual Conference for Muslim Scholars, 2025)
This qualitative study examines the implementation of maqāṣid al-sharī’ah within the Topeng Konah tradition of Bondowoso through a case study approach involving participant observation, in-depth interviews with 20 informants, and document analysis. The findings reveal that Topeng Konah serves as a sophisticated form of cultural resistance, utilizing performance symbols that integrate the principle of ḥifẓ al-bī'ah (environmental preservation) as a contemporary expansion of maqāṣid. The five primary characters—Bujang Ganong, Patih Pujangga, Prabu Kelono, Dewi Sekartaji, and Pujangga Anom—collectively reflect the implementation of ḍarūriyāt al-khams (the five essentials) in fostering social harmony within a pluralistic society. Thematic analysis identifies a three-stage value transformation: preservation, adaptation, and transformation, which converts local memories of tolerance into global messages. The study concludes that Topeng Konah is a manifestation of living maqāṣid, successfully creating a dialectic between universal Islamic values and local wisdom. This tradition offers an inclusive model of Islamic practice that remains highly relevant to the multicultural Indonesian context, demonstrating how traditional arts can facilitate the synthesis of religious law and cultural heritage.